A multi-product newsvendor problem with budget and loss constraints - Zhou, Y.; Chen, X.; Xu, X.; Yu, Changjun (World Scienfitic, 2014)
The solution space of a multi-product newsvendor problem (MPNP) with two constraints is analyzed and divided by four cases. One constraint is a loss constraint, which is nonlinear and has the integral symbol, while the other is a budget constraint. The threshold values of different solution regions are calculated and the corresponding solving methods for each case are provided, reducing the complexity of problem solving. The paper suggests the loss-based marginal utility deleting method solves non-negative constraint problems, and the linear approximate approach deals with nonlinear constraint optimal problems with an integral symbol in the model. Numerical examples are given, showing that the solving approach is more effective.